Liquid mixture control system using PLC - Abdul Rahman, Azman (2011)
The principle of the Liquids Mixture Control System By using PLC is to mix two or more types of liquids with different PH values, in order to acquire new PH value with correct composition, which to maintain product quality .These processes exist in beverage, drinkingwater, food, pharmaceuticals, chemistry, refinery indutries, also important for fish hatcheries, water conditioning and aquaculture, etc, moreover correct composition of PH value in our diet is important for our health,therefore for this project, volumetric of one type of liquid,can be determined its quantity of volume before entering into the Mixture tank and then, another liquid is entered automatically into this Mixture Tank,after that the mixing process will be done,which this system determined PH value automatically that macthing the PH value requirement as a complete product.Programmable Logic Controller (PLC) with analogue input signal is used to control this Liquids Mixture Control system.This system consist of six tanks, with one mixturer motor and also five pumps are used to control the system via PLC. PH sensor is used to detect PH value of the mixture, which this signal is fed to analogue input PLC teminal, that to be used for comparing PH value required as a product. The user can select volume one type of liquid to be entered into Mixture Tank, by pressing select buttons on the control panel board.This project can be used for manufacturing industries base on liquids and also for fish hatcheries, water conditioning and aquaculture ,which have been proved by project analyzing and testing results.